Investigation of SNP rs2060546 Immediately Upstream to NTN4 in a Danish Gilles de la Tourette Syndrome Cohort - Padmanabhuni, Shanmukha S.; Houssari, Rayan; Esserlind, Ann-Louise; Olesen, Jes; Werge, Thomas M.; Hansen, Thomas F.; Bertelsen, Birgitte; Tsetsos, Fotis; Paschou, Peristera; Tümer, Zeynep (Frontiers in Neuroscience, 2016)
Gilles de la Tourette syndrome (GTS) is a neuropsychiatric disorder characterized by multiple motor and vocal tics. GTS is a complex disorder, with environmental factors and several genes involved. Although variations within a few genes such as AADAC, NRXN1, SLITRK1, HDC, and IMMP2L have been tentatively associated with GTS (in a small number of patients), the causative genes underlying GTS pathophysiology remain unknown. In a previous genome-wide association study (GWAS) a single nucleotide polymorphism (SNP, rs2060546) near the Netrin-4 (NTN4 - MIM 610401) gene was shown to be associated with GTS [odds ratio (OR) = 1.7; p-value = 5.8x10-7] thus warranting further investigations. As NTN4 is one of the axon guidance molecules expressed in the central nervous system and it interacts with encoded protein of SLIT and WNT genes guiding the growth cone towards its target, it is an attractive candidate susceptibility gene for GTS. In this study we attempted to replicate the association of rs2060546 with GTS by genotyping a cohort of 240 Danish GTS patients and 1007 healthy controls. Our results did not reveal an association (OR= 1.363; p-value = 0.3329) in the Danish cohort alone, which may be due to the small sample size. However, a meta-analysis including the present cohort and a total of 1316 GTS patients and 5023 controls from GTS GWAS Replication Initiative (GGRI) and the first GTS-GWAS yielded a significant signal (OR = 3.74; p-value = 0.00018) and same direction of effect in the three cohorts. Thus, our study strengthens the evidence of the possible involvement of NTN4 in GTS etiology, suggesting that further studies in even larger samples and functional studies are warranted to investigate the role of this region in GTS pathogenesis.